Differences in Tissue Factor Positive Microparticle (Tf+Mps) Levels in Breast Cancer Patients Before and After Chemotherapy - Adnyana, I Wayan Losen; Rahayu Srikandi, Ni Made Putri (http://dharmais.co.id/, 2025)
Background: Cancer-associated thrombosis is a well-known phenomenon that leads to significant patient morbidity and mortality. Malignancy increases the risk of thrombosis, and chemotherapy further elevates this risk. The pathophysiological mechanisms underlying this process are still poorly understood. High levels of tissue factor positive microparticle (TF+MPs) are a risk factor for thrombosis, with levels increasing in patients with cancer. This study aims to find the impact of chemotherapy on TF+MPs levels in breast cancer patients before and after chemotherapy. Method: This longitudinal observational analytic study involved breast cancer patients undergoing chemotherapy at Prof. Dr. I.G.N.G. Ngoerah General Hospital (RSUP), Denpasar, from March to August 2024, in patients above 18 years of age. TF+MPs levels were measured using the Enzyme-linked Immunosorbent Assay (ELISA) method. A paired T-test analyzed the differences in TF+MPs levels in breast cancer before and after chemotherapy.Results: A total of 31 breast cancer cases undergoing chemotherapy were studied. The average age of breast cancer patients was 51.16 ± 6.93 years. No Special Type breast cancer (61.3%) was the dominant type found. Stage III was predominantly observed in breast cancer patients (38.8%), and poorly differentiated grading had a high percentage in breast cancer cases (51.8%). The median body mass index (BMI) of breast cancer patients was 24.3 (18.0-39.7) kg/m². The levels of TF+MPs showed a significant difference in breast cancer patients before chemotherapy, measured at 0.42 ± 0.17 pg/mL, and after undergoing chemotherapy, measured at 0.66 ± 0.28 pg/mL. This represents an increase in TF+MPs levels of 0.24±0.28 pg/mL as observed in a paired t-test (p 0.001).Conclusion: This study demonstrates that chemotherapy significantly increases the levels of TF+MPs in breast cancer patients. Further study is warranted to investigate the clinical implications of monitoring TF+MPs for thromboprophylaxis strategies